Ações de inovação em bibliotecas universitárias : análise focada no Sistema de Bibliotecas da Universidade Federal de Campina Grande (UFCG) - Silva, Marly Felix da (2024)
This study addresses the theme „Actions of Innovation in University Libraries‟ focusing on the Library System of the Federal University of Campina Grande (UFCG). Explored innovative initiatives and practices implemented in UFCG libraries, analyzing their impact and relevance in the academic context. These actions may range from the adoption of new technologies to the implementation of services and strategies that optimize access and management of innovation. Innovation has stood out as a primordial factor for the development, optimization, and excellence of higher education, especially in activities linked to the triad: teaching, research, and extension. Considered as equipment and informational support for the academic community, discussions that deal with actions of innovation in informational spaces in university libraries have become recurrent, as these equipment provide, through their collection, access to the most various sources of information in physical or virtual format. University libraries have adopted the use of new innovative technological tools and products (goods and services) as a means to facilitate the dissemination of information and communication processes among users of the Library System of the Federal University of Campina Grande. The study problem that guides this dissertation is based on the following question: How have innovation actions applied to the UFCG System Library contributed to facilitating users' autonomous access to the information resources available in libraries? Based on the problem presented, this study aimed to analyze the actions of innovation implemented in the Library System of the Federal University of Campina Grande your contributions to users‟ autonomous access to information resources. Regarding methodological route, it will be Survey research, conducted in the form of descriptive and exploratory research, with a quantitative and qualitative approach to data analysis, involving bibliographical and documentary, predicted for the application of an on-line questionnaire with the documentary librarians who are part of UFCG System Library staff. The obtained results highlighted the relevance of implementing actions of innovation in the highlighted System, not only for providing better information resources and services to the academic community but also for strengthening the role of Information Science and Librarianship in promoting access to information and building a more informed, inclusive and technologically advanced society. It is concluded that the research findings reinforce the pressing need for adaptation and evolution, which promote the modernization of technological infrastructure, the implementation of efficient management systems, and the continuous training of librarian professionals. Also, the need for a proactive and guiding approach to innovation in the management of UFCG libraries, aiming to implement innovative actions not only as an informational need but also as an opportunity to transform UFCG libraries into true agents of excellence in supporting teaching, research, and extension.